Faculty Perceived Benefits and Barriers of Online Teaching among Nursing Faculty in Tamil Nadu (International Journal of Nursing Education, 2020)
The Covid- 19 pandemic has forced the central and state governments to strictly adhere to completelockdown in the country. In order to continue teaching and learning of Nursing students, Online learningwas organized by Tamil Nadu Nurses and Midwives Council (TNNMC), in collaboration with nursingeducational Institutions of Tamil Nadu. This study was undertaken to assess the Perceived Benefits andBarriers and of online learning, among Nursing faculty in Tamil Nadu.Method: A cross sectional, descriptive correlational study was conducted among 2375 faculty, who wereselected through consecutive sampling technique, in nursing colleges of Tamil Nadu. Google survey formswere used to collect the data (Rating Scales on Perceived Benefits and Barriers of online learning).Results: Study findings revealed that, Mean scores of benefits of online learning is 80/100, (SD - 9.1)andbarriers scores was 62/100 (SD-9.24).Conclusion: Overall study findings revealed that overall faculty had positive perception on benefits of onlinelearning even though they were also concerned about some barriers which can be managed by meticulousplanning and implementation of the system. Therefore it can be effectively incorporated in future also alongwith traditional teaching method to facilitate effective teaching and learning process.